Design of Monitoring and Telecontrol System on Cassava Fermentation as Basic Ingredients of Mocaf Flour (Modified Cassava Flour) Based on Internet of Things (IoT) - Dayu Putra, Rosario Febry; Hadiwiyatno, Hadiwiyatno; Hidayati, Nurul (Jurnal Jaringan Telekomunikasi, 2023)
Mocaf (Modified Cassava Flour) is flour from cassava which is fermented by lactic acid bacteria. The growth temperature for lactic acid bacteria is 30°C-37°C with a fermentation time of 12-24 hours. In previous research, during 24 hours of fermentation at 33°C, mocaf flour produced the highest protein content of 12.87% without using a temperature stabilization system. The success of the fermentation process is indicated by a decrease in the pH value of the fermentation water to 4.5–5.0. In household scale producers, mocaf fermentation is still carried out traditionally at unstable temperatures. Therefore, a system is needed to monitor and control temperature automatically. In this research, the system that has been designed uses an ESP32 microcontroller as the system control center. The pH sensor is used to detect the pH value of water, the gas sensor is used to detect carbon dioxide gas (CO2) and the temperature sensor is used to detect the water temperature value. Peltier elements are used to lower the temperature and heaters are used to increase the temperature of the fermented water. In this research, a successful fermentation process with a pH value of around 5.0 could be achieved within ±12 hours at a temperature of 33°C, ±18 hours at a temperature of 43°C, and ±25 hours at a temperature of 23°C. In this study the mocaf fermentation process was completed in only ± 12 hours at a temperature of 33°C which is the ideal temperature for the growth of lactic acid bacteria.